Relationship between metabolic parameters and stroking technique characteristics in front crawl. - Wakayoshi, K.; D'Acquisto, J. D.; Cappaert, J. M.; Troup, J. P. (1996)
At aerobic intensities stroking techniques are relatively constant. At anaerobic intensities they are altered as are the nature of the physiological energy requirements.